Push or Pull? Policy Barriers and Incentives to the Development and Deployment of CO2 Utilization, in Particular CO2 Mineralization - Olfe-Kräutlein, Barbara; Strunge, Till; Chanin, Anna (Frontiers in Energy Research, 2021)
Like other hard-to-abate sectors, the cement and concrete industry is facing growing pressure to reduce CO2 emissions. In this context, the carbonation of minerals or industrial wastes with CO2 (CO2 mineralization) is attracting growing interest in research and industry as well as among policy makers. Despite their technical feasibility, few of these innovative carbon capture and utilization (CCU) technologies have so far reached the commercialization stage. Due to their low maturity and potentially higher market prices, these technologies presently require policy support in order to realize their full sustainability potentials. This paper elucidates which policies are considered appropriate, in the literature, for fostering the further development and implementation of CCU technologies and thus achieving the sustainability potential of CO2 mineralization applications. First, we performed a meta-analysis of recent literature in order to identify policies and measures that potentially represent barriers or incentives to the development and deployment of CO2 mineralization technologies, and categorized them as technology-push or market-pull policies. As a second step, we conducted an online survey of policy-making priorities among experts in the field. This identified numerous relevant policies, of which the majority are market-oriented. While most existing market-pull policies do currently not support CCU technologies and would require adaptation to do so, technology-push policies already provide support for their development. However, while the need for technology-push support in the early development phases is still continued, the broad spectrum of market-pull policies that are considered relevant shows that a shifting focus of policy support is required to better address the current state of development of CO2 mineralization technologies and their upcoming market entry.